Sistem pengelolaan Embarkasi dan Debarkasi di Unit Pelaksana Teknis Asrama Haji Bekasi - Detaliani, Yunika Detaliani; Yuningsih, Yuyun; Sutisna, Dede (Mabrur: Academic Journal of Hajj and Umra, 2024)
The purpose of this research is to find out the system of planning, organizing, implementing, and supervising the embarkation and debarkation of pilgrims at the Bekasi Hajj Dormitory UPT in 2024, as well as to find out what are the inhibiting and supporting factors in the implementation of embarkation and debarkation at the Bekasi Hajj Dormitory UPT, this thesis uses a qualitative method, and uses the theory of management functions according to George R. Terry. The results of this research are comprehensive planning, structured organization of human resources, implementation by implementing effective One Stop Service, and strict supervision are the main keys to ensure the smooth and efficient process of departure and repatriation of pilgrims. Each stage involves coordination between various parties, the use of information technology, and anticipation of potential obstacles such as bad weather and budget constraints. Keywords: Hajj pilgrims; Management; System